Unequal Classrooms: Online Higher Education and Non-Cognitive Skills - Morton, Jennifer M. (Philosophical Inquiry in Education, 2016)
In this paper, I reflect on the changing role of higher education by focusing on the case of online education. I consider the promise of online education as a means to mitigate educational inequalities. Based on the available empirical evidence, I argue that this promise is unlikely to be fulfilled because online education is not well-suited to develop the social and emotional skills needed by students from low-income and minority backgrounds for social mobility. Nonetheless, the changing social, political, and economic role of the university should lead us to revise the classical vision of the university’s aims. I argue that the aim of the university should be sensitive to its new social, political, and economic role without falling prey to coarse pragmatism. This third approach delicately navigates the middle-ground between idealism and pragmatism.